Is Carbon Tax Truly More Salient? Evidence from Fuel Tourism at the France-Germany Border - Odran Bonnet; Étienne Fize; Tristan Loisel; Lionel Wilner (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper exploits the introduction of the German carbon tax in 2021 as well as excise tax rebates on fuel in both France and Germany, consecutive to the 2022 oil crisis, to infer how fuel tourism responds to changes in relative prices. Based on French high-frequency transaction-level data issued from individual banking accounts, we find substantial displacement between foreign and domestic consumption. When relative prices increase by 1%, the relative cross-border demand decreases by 7.7%. In border areas, the elasticity of tax revenue with respect to foreign prices is as high as 0.5. Moreover, there is no substantial difference in demand response to either carbon or excise tax. Such empirical evidence illustrates the importance of coordinating tax policy within EU.
Keywords: H20; H23; H77; R48; 330; commodity taxation; tax coordination; carbon pricing; fuel tourism; transaction-level data